2015
DOI: 10.1039/c5ra06242j
|View full text |Cite
|
Sign up to set email alerts
|

Salen based Schiff bases to flame retard thermoplastic polyurethane mimicking operational strategies of thermosetting resin

Abstract: A classical Schiff base N,N 0 -bis(4-hydroxysalicylidene)ethylenediamine (L2), a member of the Salen group that has been introduced as a non-phosphorus and non-halogen flame retardant in thermoplastic polyurethane (TPU) is found to operate in an intriguing way to fire retard the material. L2 blended with TPU significantly improves the inherent flammability of TPU without a synergist. A plausible mechanism including intermediates in the reinforcement of this elastomer towards flame retardancy is elaborated in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 37 publications
(80 reference statements)
5
30
0
Order By: Relevance
“…On the other hand, TGA results ( Figure 1C) shows that there was interaction between LFX and TPU. Similar behaviour was reported when TPU was combined with tetracycline, ciprofloxacin or Schiff base additives [14,33,34]. It has been proposed that the C=O groups present in the TPU urethane groups can stablish non-covalent interactions with the drug.…”
Section: Discussionsupporting
confidence: 66%
“…On the other hand, TGA results ( Figure 1C) shows that there was interaction between LFX and TPU. Similar behaviour was reported when TPU was combined with tetracycline, ciprofloxacin or Schiff base additives [14,33,34]. It has been proposed that the C=O groups present in the TPU urethane groups can stablish non-covalent interactions with the drug.…”
Section: Discussionsupporting
confidence: 66%
“…The first stage (around 290 °C) is the degradation of hard segments, forming isocyanates and alcohols, primary or secondary amines, olefins, and carbon dioxide. The second stage (around 390 °C) corresponds to the thermal degradation of soft polyol segments, which is characterized by the formation of a melt pool and rapid weight loss . There is no char remaining beyond 600 °C, indicating complete degradation of polyurethane.…”
Section: Resultsmentioning
confidence: 99%
“…The second stage (around 390 °C) corresponds to the thermal degradation of soft polyol segments, which is characterized by the formation of a melt pool and rapid weight loss. [37,38] There is no char remaining beyond 600 °C, indicating complete degradation of polyurethane. The coatings do not delay the initial degradation of PUF, but significantly reduce its thermal degradation at the later stages where the mass loss is more than 20%.…”
Section: Thermal Stability Of Coated Foammentioning
confidence: 99%
“… Other studies on Salen‐based flame retardants in TPU have also been reported. Although Salen‐type Schiff base derivatives can be used to produce flame‐retarding polymers,the thermal cross‐linking process of the Salen component mainly occurs in the condensed phase and has no significant effect on the gas‐phase during the combustion of polymers.…”
Section: Introductionmentioning
confidence: 99%